PENINGKATAN PROFESIONAL GURU MELALUI KOMUNIKASI INFORMAL - Sri Handayani (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2015)
Abstract: The study was aimed at describing (1) the process and the components of informal communication in improving the teachers’ professionalism, and (2) the informal communication model in improving the professionalism of elementary school teachers in Jember Regency. The research method used was qualitative with phenomenological approach which was multi-site study on three elementary schools. The data was collected by interviewing, observing, and documenting. The data analysis was carried out by using flow and constant comparative models. The results showed the improvement of the teachers’ professionalism through the process and the components of informal communication including cognitive, affective, and psychomotor aspects. The informal communication model in improving the teachers’ professionalism on this case (1) was in the form of direct interactive model, (2) was in the form of indirect interactive model, and case (3) was in the form of direct and indirect interactive model. Abstrak: Penelitian bertujuan mendeskripsikan (1) proses dan komponen komunikasi informal dalam meningkatkan profesional guru; dan (2) model komunikasi informal dalam meningkatkan profesional guru di SD Kabupaten Jember. Metode penelitian kualitatif, pendekatan fenomenologis, dengan rancangan studi multi kasus pada tiga Sekolah Dasar. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Analisis data menggunakan model alir dan comparative constant. Hasil penelitian menunjukkan peningkatan professional guru melalui proses dan komponen komunikasi informal meliputi aspek kognitif, afektif, dan psikomotor. Model komunikasi informal dalam meningkatkan profesional guru pada kasus (1) adalah interaktif langsung, (2) dengan model interaktif tidak langsung, dan kasus (3) dengan model interaktif langsung dan tidak langsung.